Do High Rates of Atypical Glandular Cells Correlate With Higher Incidence of Disease in a Large Safety Net Hospital. Issue 4 (October 2020) - Kuhn, Theresa; Finneran, Catherine; Kohut, Adrian; Wang, Emily; Birdsong, George; Krishnamurti, Uma; Mosunjac, Marina; Tadros, Talaat; Oprea, Gabriela; Avadhani, Vaidehi; Boguslawski, Shae; Karlow, Samantha; et al.
Abstract : Objective: The aim of the study was to describe the incidence and correlates of atypical glandular cell (AGC) Pap tests in a low socioeconomic status, underserved population. Materials and Methods: Medical records of patients with AGC Pap tests at a single institution were reviewed from January 2013 to August 2019. Baseline characteristics were extracted including age, body mass index, birth control, abnormal uterine bleeding, and human papillomavirus (HPV). All colposcopy and endometrial biopsies were classified into negative/low-risk (polyps, tubular metaplasia, microglandular hyperplasia, cervical intraepithelial neoplasia 1) and high-risk (HR) lesions (cervical intraepithelial neoplasia 2/3, adenocarcinoma in situ, endometrial hyperplasia, cervical cancer, endometrial cancer). Logistic regression identified significant associations. Sixty-eight randomly selected AGC cytology slides from the cohort and 32 non-AGC slides outside the cohort were blindly reviewed by 6 pathologists. Fleiss κ interrater agreement was assessed. Results: Seven hundred forty patients with AGC Pap tests were identified (0.8% of all Pap tests performed during this time). After excluding for incomplete data, 478 patients were included. Sixty-three patients had HR lesions (13.3%). Patients with HR lesions had increased odds of abnormal uterine bleeding (odds ratio = 4.32, p < .001) and HPV positivity (odds ratio = 10.89, p < .001) when compared with patients with low-risk lesions. The κ agreement was 0.21 for all cases and 0.18 for AGC alone. Conclusions: This population falls within the national averages for AGC Pap tests. There was an increased risk of HR lesions in patients with abnormal uterine bleeding and HPV positivity. The rate of HR lesions among AGC Pap tests was at the lower end of values in the literature. After blinded pathologist review, interobserver κ agreement was low for AGC Pap tests.